ASSOCIATION OF GLUTATHIONE-S-TRANSFERASE M1/T1 GENOTYPES WITH AIRWAY REMODELING IN CHILDREN WITH BRONCHIAL ASTHMA - Koloskova, O.K.; Tarnavska, S.I.; Bilyk, G.A. (World of Medicine and Biology, 2023)
In this work, a study of individual clinical, laboratory and spirographic features of bronchial remodeling in children with bronchial asthma with an alternative GSTT1 and GSTM1 genotype was carried out. It has been established that in children with bronchial asthma, deletions and the null genotype of GSTT1 and GSTM1 are associated with worse spirographic indices of disease control (odds ratio – 4.0). The presence of bronchial remodeling markers (MMP-9, VEGF) in sputum is associated with deletion polymorphism or null genotype of GSTT1 and GSTM1, since such patients have a significantly higher risk of airway restructuring, which reflects the accumulation of MMP-9 > 5.4 ng/m (odds ratio – 3.0) and VEGF more than 143.2 ng/mL (odds ratio – 3.9).
Keywords: bronchial asthma; children; MMP-9; VEGF; GSTT1; GSTМ1